2019
DOI: 10.1016/j.biomaterials.2019.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-mediated intratumoral inhibition of miR-21 for improved survival in glioblastoma

Abstract: Glioblastoma (GBM) is the most common and deadly form of malignant brain tumor in the United States, and current therapies fail to provide significant improvement in survival. Local delivery of nanoparticles is a promising therapeutic strategy that bypasses the blood-brain barrier, minimizes systemic toxicity, and enhances intracranial drug distribution and retention. Here, we developed nanoparticles loaded with agents that inhibit miR-21, an oncogenic microRNA (miRNA) that is strongly overexpressed in GBM com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 40 publications
3
62
0
Order By: Relevance
“…Among those miRNAs previously described to have a role in the regulation of molecular mechanisms of oxidative stress, some of them have been suggested as therapeutic targets. For example, miR-21-conjugated NPs has been assessed in glioblastoma treatment [154,155]. Specifically, Seo and colleagues demonstrated that both RNA-based anti-miR-21 conjugated with a cationic Poly(Amine-Co-Ester) (PACE) and Peptide Nucleic Acid (PNA) anti-miR-21 conjugated with a copolymer of Poly(Lactic Acid) and Hyperbranched Polyglycerol (PLA-HPG), provided an efficient intracellular delivery system to inhibit miR-21 expression, leading to PTEN upregulation and apoptosis of human GBM (Glyoblastoma Multiforme) cancer cells.…”
Section: Clinical Advancements Of Mirna-based Drugsmentioning
confidence: 99%
“…Among those miRNAs previously described to have a role in the regulation of molecular mechanisms of oxidative stress, some of them have been suggested as therapeutic targets. For example, miR-21-conjugated NPs has been assessed in glioblastoma treatment [154,155]. Specifically, Seo and colleagues demonstrated that both RNA-based anti-miR-21 conjugated with a cationic Poly(Amine-Co-Ester) (PACE) and Peptide Nucleic Acid (PNA) anti-miR-21 conjugated with a copolymer of Poly(Lactic Acid) and Hyperbranched Polyglycerol (PLA-HPG), provided an efficient intracellular delivery system to inhibit miR-21 expression, leading to PTEN upregulation and apoptosis of human GBM (Glyoblastoma Multiforme) cancer cells.…”
Section: Clinical Advancements Of Mirna-based Drugsmentioning
confidence: 99%
“…More recently, high levels of apoptosis on glioma cell lines were obtained following co-treatment with two PNAs, one targeting miR-221-3p, the other targeting miR-222-3p. In addition, Seo et al [113] showed the use of a PNA targeting miR-21 as in vivo inhibitor of glioma U87 cells.…”
Section: Peptide Nucleic Acid-mediated Targeting Of Micrornas In Gbm mentioning
confidence: 99%
“…As far as delivered PNAs in vivo to experimental models of GBM, local delivery of nanoparticles should be considered a promising therapeutic strategy that bypasses the blood-brain barrier, minimizes systemic toxicity, and enhances intracranial drug distribution and retention. In this respect, Seo et al [113] developed nanoparticles loaded with PNAs inhibiting miR-21, a microRNA overexpressed in GBM and retaining oncogenic features. These authors employed a block copolymer of poly(lactic acid) and hyperbranched polyglycerol to deliver an anti-miR-21 PNA, showing that efficient intracellular delivery was facilitated, leading to miR-21 suppression and PTEN upregulation and apoptosis of human GBM cells.…”
Section: Final Remarks On Mirna Therapeutics Based On Pna Molecules: mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a positive therapeutic effect was only observed in peripheral tumors, but not in intracranial tumors, pointing towards the inability of CPA-7, like many small molecule therapeutics and biomolecules, to cross the protective BBB and enter the brain tumor compartment. 6 A wide range of nanoparticles have been developed to deliver chemotherapeutic drugs, such as docetaxel, [11][12][13] paclitaxel, [14][15][16] doxorubicin 17 or other small molecule chemotherapeutics; [18][19][20][21][22] or, to leverage antibodies, 23,24 RNA, [25][26][27][28] or peptides 29 in an attempt to enhance GBM therapy.…”
mentioning
confidence: 99%